Implikasi Ajaran Yoga Bagi Pamangku di Bali dalam Aspek Tri Sarira - Nerta, I Wayan (Jurnal Penelitian Agama Hindu, 2023)
The Patanjali Sutra Yoga teachings are not only gestures but also give the mandate to the existence of body and mind. A priest at the time of nganteb upakara was likened to a "mayoga" (in Balinese) that is, carrying out parts of the yoga teachings. The body is not only a construction of skeletal bones, muscles, flesh, and organs themselves. But the body can be seen and interpreted from several points of view. In Hinduism, there are three layers of the human body called Tri Sarira, namely sthula sarira, suksma sarira, and antahkarana sarira. The purpose of this article is to find out the implications of yoga teachings for the priest in the aspect of Tri Sarira. This research uses a qualitative approach with an interpretive paradigm. The results of this study show that the yoga teachings for the priest in Bali meaningfully have implications for physical and psychological influences on three layers of the body called Tri Sarira, namely sthula sarira (rough body), suksma sarira (subtle body), and antah karana sarira (causative body). The yogic teachings practiced by religious leader on sthula sarira (rough body) have implications on the body such as an upright sitting posture. Therefore, getting into the habit of taking a comfortable sitting posture upright for the priest will reduce symptoms and improve the bending of the spine. The yoga teachings practiced by the priest on suksma sarira (subtle body) have implications for inner satisfaction for the priest for being able to help others. The yoga teachings practiced by the priest in the middle of nowhere karana sarira (causal body) have implications for increasing awareness of the quality of life as a human being because it is an obligation to always be ethical and do good in serving the people. So, it can be concluded that the teachings of yoga have implications for the activities of the priest.